Current status of cross-linking and blending approaches for durability improvement of hydrocarbon-based fuel cell membranes. (29th March 2022) - Mirfarsi, Seyed Hesam; Parnian, Mohammad Javad; Rowshanzamir, Soosan; Kjeang, Erik
Abstract: Due to the demand for developing reliable and economical fuel cells, many researchers have focused on durability improvement of hydrocarbon-based proton exchange membranes (PEMs), without compromising performance. Among various techniques, cross-linking and blending show promising potentials by introducing physical and/or chemical bonds between polymer chains and creating a 3D network within their structure. Cross-linking is accomplished through thermal, solvothermal, radiation-assisted, and cross-linker assisted methods, whereas blending is categorized based upon the existing interactions between polymers, namely acid-acid, acid-base, and charge transfer network. This review article discusses the recent achievements of cross-linked and blend hydrocarbon-based PEMs in long-term stability tests and durability studies. Additionally, their salient dimensional, thermo-chemical, and transport properties are highlighted, including the in-situ fuel cell performance and electrochemical diagnostics. Accordingly, cross-linked and blend membranes have shown over 4000 h durability in hydrogen fuel cells and more than 100 times lower methanol cross-over compared to conventional fluorinated membranes, implying significant potential for commercialization. Highlights: Durability of cross-linked and blend hydrocarbon-based membranes is reviewed. Different methods of membrane preparation are comprehensively discussed. Cross-linking and blending create chemical and physical bonds in polymer structure. They have shown more than 100 times lower methanol cross-over than PFSA membranes. Over 4000 h stability obtained in H2 fuel cell under steady/accelerated condition.